2020
DOI: 10.3329/nimcj.v10i2.45435
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome of Lichtenstein technique for complete variety of inguinal hernia repair in a tertiary care hospital

Abstract: Background : Inguinal hernia repair is very common in day to day general surgical practice. Result of surgical repair is often satisfactory but recurrences following surgery are troublesome both for the surgeon and the patient. Lichtenstein technique is now the most widely performed technique in groin hernia repair.Objective : The aim of this study was to assess short term outcome of complete variety of inguinal hernia repair by Lichtenstein technique. Methodology :This was a prospective observational study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…It is reflected very well in this study where most of the patients (61%) were in low saocioecenomic status, 24% and 15% were in middle and higher socioecenomic catagories respectively. In this study, right inguinal hernias were more common than left, ratio 1.08:1 and only 6% cases were bilateral which correlates with study done by Mukesh sangwan [8] et al showed 1.45:1 and with also some other studies [7,5,17] In our study, direct hernias, indirect pantaloons hernias seen were in 57%, 30%, 7% study patient respectly and the present study correlated well with Burcharth et al [4] In our study population, older age (50%) and smoking (39%) were the most common risk factors present. History of prostatism (19%), heavy weightlifting(21%),constipation(17%) were the other common risk factors for the development of inguinal hernia in our study(Figure 5) that correlates with study of Robindera Kour et al [10] and some other studies 3,5,7 . Smoking was established as an independent risk factor for hernia development with Malviya et al [1] reporting 30.6%10 of their study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It is reflected very well in this study where most of the patients (61%) were in low saocioecenomic status, 24% and 15% were in middle and higher socioecenomic catagories respectively. In this study, right inguinal hernias were more common than left, ratio 1.08:1 and only 6% cases were bilateral which correlates with study done by Mukesh sangwan [8] et al showed 1.45:1 and with also some other studies [7,5,17] In our study, direct hernias, indirect pantaloons hernias seen were in 57%, 30%, 7% study patient respectly and the present study correlated well with Burcharth et al [4] In our study population, older age (50%) and smoking (39%) were the most common risk factors present. History of prostatism (19%), heavy weightlifting(21%),constipation(17%) were the other common risk factors for the development of inguinal hernia in our study(Figure 5) that correlates with study of Robindera Kour et al [10] and some other studies 3,5,7 . Smoking was established as an independent risk factor for hernia development with Malviya et al [1] reporting 30.6%10 of their study.…”
Section: Discussionsupporting
confidence: 90%
“…Hernia is a Latin term that is defined as an "abnormal protrusion of a viscus or part of a viscus through a normal or abnormal opening in the wall of its containing cavity". 1Still now nguinal hernia repair is second most common general surgical operations worldwide that account for about 10-15% of all surgical procedures [7,17] . It is very common in men with lifetime risk of 27% and 3% for women, thus 1 in 4 men has the risk of developing the condition.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations